Mengapa Wisatawan Berminat Mengunjungi Kabupaten Buleleng? : Kajian Pengalaman Gastronomi, Citra Destinasi dan Kepuasan Wisatawan - Chiselia, Kadek Aprilda; Irwansyah, M. Rudi (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This study aims to determine the influence of gastronomic experience, destination image and tourist satisfaction on interest in visiting Buleleng Regency. The population in this study is tourists who are visiting Buleleng Regency. The number of samples used in this study was 126 respondents. The sampling technique in this study uses the purposive sampling technique. The data in this study was collected by distributing questionnaires. The data processing in this study uses SPPS version 26.0. The analysis techniques used are path analysis and determination coefficient (R2). The results of this study show that: (1) Gastronomic experience has an effect on the interest of tourists to revisit Buleleng Regency. (2) The image of the destination affects the interest of tourists to revisit Buleleng Regency. (3) Tourist satisfaction affects the interest of tourists to revisit Buleleng Regency. (4) Gastronomic experience affects the interest of tourists to revisit Buleleng Regency through the image of the destination. (5) Gastronomic experience has an effect on the interest of tourists returning to Buleleng Regency through tourist satisfaction. (6) Gastronomic experience, destination image and tourist satisfaction affect the interest in visiting Buleleng Regency.